In vivo dosimetry for head ct examinations in paediatric patients. (September 2016) - Stathopoulos, Ioannis; Ploussi, Agapi; Syrgiamiotis, Vasileios; Makri, Triantafillia; Hatzigiorgi, Christiana; Carinou, Eleftheria; Sakellaropoulos, George; Panayiotakis, George S.; Efstathopoulos, Efstathios P.
Abstract : Introduction: Serious concerns about children exposure to ionizing radiation have been raised due to the widespread use of computed tomography (CT) in paediatrics. The increased radiosensitivity of children and the radiation-associated cancer risk call for immediate action in the field of patient-specific dosimetry and optimization of existing CT protocols. Purpose: The main objective of our study is to present in vivo radiation dose measurements during paediatric head CT examinations using thermoluminescent dosimeters (TLDs). To our knowledge, there are limited literature data concerning in vivo dosimetry in paediatric patients. Materials and methods: The ongoing study includes paediatric patients ranging from neonates to 15 years old who underwent head CT examinations on a 16-slice CT scanner in ''Agia Sofia" Children's Hospital in Athens using iterative reconstruction algorithm. LiF:Cu, P TLDs, properly calibrated, were placed in eyes, forehead, behind ears and thyroid glands. Surface doses to the lens of the eye, the brain and the thyroid were calculated for each patient. Results: For patients ⩽5 years old, surface doses in eye lens, brain and thyroids were 38.45 ± 5 mGy, 33.69 ± 14.05 mGy and 1.84 ± 0.48 mGy respectively, while for patients >5 years old, the surface doses were 35.56 ± 11.16 mGy, 40.04 ± 7.67 mGy and 2.05 ± 0.32 mGy respectively. Conclusion: Although there are many challenges, patient-specific dosimetry is of great importance in paediatric patients. In vivo dosimetry is a powerful tool which provides an accurate and effective method for skin dose measurements. Furthermore, since the eyes and the thyroid are superficial organs, the calculated surface dose can give a good estimation of the organ dose to ocular lens and thyroid gland. Disclosure: None.